MicroRNAs and the adolescent brain: Filling the knowledge gap. (November 2016) - Rao, Yathindar S.; Pak, Toni R.
Highlights: This review gives a brief summary of miRNA biogenesis and function in the brain. The impact of hormones on miRNA function are discussed. MiRNA function during puberty could be distinct from other developmental stages. Abstract: Over two decades ago the discovery of microRNAs (miRNA) broadened our understanding of the diverse molecular pathways mediating post-transcriptional control over gene expression. These small non-coding RNAs dynamically fluctuate, temporally and spatially, throughout the lifespan of all organisms. The fundamental role that miRNAs have in shaping embryonic neurodevelopment provides strong evidence that adolescent brain remodeling could be rooted in the changing miRNA landscape of the cell. Few studies have directly measured miRNA gene expression changes in the brain across pubertal development, and even less is known about the functional impact of those miRNAs on the maturational processes that occur in the developing adolescent brain. This review summarizes miRNA biogenesis and function in the brain in the context of normal (i.e. not diseased) physiology. These landmark studies can guide predictions about the role of miRNAs in facilitating maturation of the adolescent brain. However, there are clear indicators that adolescence/puberty is a unique life stage, suggesting miRNA function during adolescence is distinct from those in any other previously described system.